Administración de inventarios ABC para mejorar la gestión de almacenes en la Empresa Zicsa Contratistas Generales S.A.C., en Retamas - Parcoy - Pataz, 2014. - Monzon Calderón, Oswaldo (2015)
This thesis has been conducted in the village of Brooms , Parcoy district , province of Pataz , in the region of Libertad, Peru . The research question is how the ABC Inventory Management Warehouse Management improves the company Zicsa General Contractors. In terms of methodology, we worked with two populations and an equal number of samples, one consisting of 10 heads of guard in the production area, and one in 28 workers in the warehouse area, and in addition an interview was made the head area warehouse. Once the data is collected, we have been processed the results that have allowed qualify the study variables with indicators, after performing the corresponding analysis has been carried out discussion of this thesis. The overall objective research: "support how the ABC Inventory Management can improve Warehouse Management that company", as the specific objectives have been achieved satisfaction. Similarly, it has been possible to demonstrate the validity of the hypothesis: "The Inventory Management ABC, by categorizing the items according to their number and total cost required, improves Warehouse Management Business Zicsa General Contractors SAC, in Retamas - Parcoy - Pataz, 2014". Finally they formulated the conclusions and recommendations. The main conclusion states that the current Inventory Management despite using software, there are problems in reconciling amounts of physical inventories with translations of the system, poor physical organization of the warehouse, and neglect in recording data in the system, staff lacking training and lack of a coherent approach to decision making. It is recommended to apply the ABC model, which allows management and responsible , a basis for decision making giving more attention and importance to articles in categories A , then B , and finally C , on the efficiency of use, lost, spills, accidents , and especially the relative cost control .